Systematic Literature Review (2016–2026): Integration of IoT-Based Project-Based Learning in Physics Instruction to Develop Critical Thinking: - Dona febri Enjelina; Bambang Subali (Universitas Tidar, 2026)
Critical thinking skills are an essential competency in 21st-century physics education, given that many physics concepts are abstract and require in-depth analytical and problem-solving skills. The integration of the Internet of Things (IoT) through Project-Based Learning (PjBL) is seen as having the potential to effectively support the development of students’ critical thinking skills. This study aims to systematically analyze research trends regarding the application of IoT-based PjBL on students’ critical thinking skills in physics education from 2016 to 2026. The study employs a Systematic Literature Review (SLR) method in accordance with the PRISMA guidelines, combined with bibliometric analysis using VOSviewer. Article searches were conducted via Google Scholar, Scopus, and SINTA for publications from 2016 to 2026, yielding 997 articles during the identification phase. After undergoing the screening, eligibility, and inclusion phases, 90 articles were found to meet the inclusion criteria and were analyzed. The results of the study indicate that research publications tend to increase during the 2023–2025 period; the keywords “project-based learning,” “PjBL,” “STEM education,” “IoT,” and “technology integration” show strong correlations in the bibliometric map; and the most frequently studied topics include electricity and magnetism, waves and sound, as well as mechanics and motion. In general, PjBL-based IoT integration shows a positive trend toward the development of students’ critical thinking skills in physics learning.